T0901317, an LXR agonist, augments PKA-induced vascular cell calcification - Hsu, Jeffrey J. (2009)
We examined the effect of LXR agonists on vascular calcification, prevalent in atherosclerotic lesions. T0901317, an LXR agonist, augmented protein kinase A (PKA)-induced mineralization and alkaline phosphatase (ALP) activity in aortic smooth muscle cells isolated from wild-type, but not from Lxrβ(-/-) mice. A six-hour T0901317 treatment augmented the PKA-induced expression of the phosphate transporter Pit-1, a positive regulator of mineralization, suggesting a direct role. A ten-day T0901317 treatment attenuated PKA-induced expression of mineralization inhibitors, osteopontin and ectonucleotide pyrophosphatase/phosphodiesterase-1, suggesting an indirect role. The effects of T0901317 were attenuated by inhibition of ALP, Pit-1 and Rho-associated kinase, but not by inhibition of PKA. These results suggest that T0901317-augmented mineralization occurs downstream of PKA, involving both direct and indirect LXR-mediated pathways.